Indigenous fermentations theory and practice - Quiason, Sonia Narvas; Ang, Jesse O. (Quezon City Phoenix Pub., 1994)
Purpose: "To present in a concise and simplified manner the various aspects of the indigenous microbial processes which can be utilized in the preparation of different foods."
Content/s: Fermentation System Concepts. TSF Reference Model. Fermentor. Microbe. Culture Media and Inoculum Preparation. Microorganism. Anaerobes and Thermopiles. Indigenous Fermented Foods.
Keywords: Fermentation -- Handbooks, manuals, etc; Food -- Microbiology